Examining Iran's Contextual Situation Support for Applying Open Innovation Approach, the Case of Aviation Innovation System - Seyed Kamal Tabaian; Manochehr Manteghi; Jahanyar Bamdadsoofi; Seyyed Habibollah Tabatabaeian (بهبود مدیریت, 2011)
This research has examined the ability of Aviation Innovation System to apply science, technology and industrial potentials at national and international levels using Bergek et al. (2008) framework. This research with reviewing Innovation Systems literature and emphasising on sectoral Innovation System by Malerba about Open Innovation Approach introduced by Chesbrough, tries to combine them in Iran's Aviation Innovation System. Research question is "to what extent Iran's contextual situation supports the application of open innovation approach in the aviation sector?" To examine this, contextual situation affecting aviation sector has been surveyed in the framework of an STEEP Analysis. Ultimately, by concluding that Iran's contextual situation supports the application of open innovation approach in aviation sector in a high rate, it approved that Open Innovation approach can enhance effectiveness of Innovation in Aviation Sector. Some policies and solutions has been offered to enhance contextual situation for facilitating applying Open Innovation approach in Iran's Aviation Innovation System.